RASIONALITAS KONVERSI BANK KONVENSIONAL KE BANK SYARIâAH - Damanuri, Aji (Justicia Islamica, 2012)
RASIONALITAS KONVERSI BANK KONVENSIONAL KE BANK SYARIâAHÂ Aji DamanuriÂ Abstract: Shari>âah banking, for the last ten years, has increased in prosperity not only at the quantity of conventional banks but also at the count of assets and customers. This economical opportunity drives amount of conventional banks both to convert their institutions to be shari>âah banks and to open officially shari>âah platform units with their own assets. This system takes a significant question, is the conversion effected by both banker ideological factor and capitalists or pure economical rational calculation? Is a religious consideration linked to economical rationality? This paper is to elaborate the conversion using not only âchoice theoryâ (teori pilihan) but also ârational actionâ (tindakan rasional) to seek religious action possibility in a reasonable way of shari>âah banking.Â Keywords: shari>âah bank, conversion, rational action, religiosity.